Formation of Micro- and Nanostructures on the Nanotitanium Surface by Chemical Etching and Deposition of Titania Films by Atomic Layer Deposition (ALD) - Nazarov, Denis V. (Materials (Basel), 2015)
In this study, an integrated approach was used for the preparation of a nanotitanium-based bioactive material. The integrated approach included three methods: severe plastic deformation (SPD), chemical etching and atomic layer deposition (ALD). For the first time, it was experimentally shown that the nature of the etching medium (acidic or basic Piranha solutions) and the etching time have a significant qualitative impact on the nanotitanium surface structure both at the nano- and microscale. The etched samples were coated with crystalline biocompatible TiO(2) films with a thickness of 20 nm by Atomic Layer Deposition (ALD). Comparative study of the adhesive and spreading properties of human osteoblasts MG-63 has demonstrated that presence of nano- and microscale structures and crystalline titanium oxide on the surface of nanotitanium improve bioactive properties of the material.